Changes in biological parameters during composting of sewage sludge treatment plant - Kabbashi, Nassereldeen Ahmed; Ahmadun, Fakhru-Razi; Ramachandran, K.B; Azni, Idris (Academy of Agricultural Sciences, NAAS, India, 2002)
The sewage sludge used in this study was collected from Taman Sri Nanding and Taman Koperasi Indah Water Consortium treatment plants, Malaysia. The sludges had a high moisture content around 80% to 82% and a low C/N ratio of 7 to 8.5. Both sludges had more or less similar characteristics. However pH of sludge from Taman Sri Nanding was lower than that of Taman Koperasi. Sawdust had a low moisture content of 10-20% and a high C/N ratio ranging from 166.6 to 285. Hence sawdust was homogenized with the sludge to increase the C/N ratio of the sludge, which inoculated with a mixture of P. chrysosporium and Trichoderma harziamum. This also reduced the moisture content to the optimal level for composting. In a medium scale horizontal drum bioreactor, composting occurred for 21 days and one month curing, the biological parameters were monitored to evaluate the effect of sawdust on the composting process. No industrial waste or trade effluent is allowed to be discharged into Malaysia's sewerage system (Indah water, 1999).